EU-Turkish Relations : The Effect of the AKP Policy - Forýtek, Lukáš; Němec, Jan, 1980 srpen 23.-; Dvořáková, Vladimíra, 1957-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2017)
The master thesis deals with the issue of the Turkey-EU relations. The main aim of the thesis is to reveal the main causes of growing lack of interest of the Turkish government to become a member of the EU. The analysis of the Justice and Development Party s (AKP) effect on the Turkish foreign policy is covered as well. The thesis includes a theoretical part dealing with regionalism and regional integration and the phenomenon of Europeanisation. There is an analysis of the impact of Europeanisation on the candidate countries. The history of the Republic of Turkey and the roots of the AKP are covered. The thesis also works with the results of the general elections in the last decade. The history of the relations and accession negotiation between the EU and Turkey are analysed as well. Finally, the main potential causes of the deterioration of the negotiations are mentioned and analysed.
Vedoucí práce: Jan Němec
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: politologie [obor dipl. práce]; diplomové práce; master's theses